Swelling Potential of Clayey Soil Modified with Rice Husk Ash Activated by Calcination for Pavement Underlay by Plasticity Index Method (PIM) - Onyelowe, Kennedy C.; Onyia, Michael E.; Nguyen-Thi, Diu; Bui Van, Duc; Onukwugha, Eze; Baykara, Haci; Obianyo, Ifeoma. I.; Dao-Phuc, Lam; Ugwu, Hyginus U. (Advances in Materials Science and Engineering, 2021)
Volume change in expansive soils is a problem encountered in earth work around the world. ,is is prominent with hydraulically bound structures or foundations subjected to prolonged moisture exposure. ,is behavior of clayey used as subgrade, foundation, landfill, or backfill materials causes undesirable structural functionality and failures. To prevent this happening, clayey soils are studied for possible volume change potential and degree of expansion. Consequently, the problematic soils are stabilized. In this work, the stabilization of clayey highly expansive soil classified as A-7-6 soil and highly plastic with high clay content was conducted under laboratory conditions. ,e treatment exercise was experimented using quicklime-activated rice husk ash (QARHA), hydrated lime-activated rice husk ash (HARHA), and calcite-activated rice husk ash (CARHA) at the rates of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%. Upon treatment with the three calcium compounds to produce three sets of treated experimental specimens, the plasticity index was observed and recorded and swelling potentials were evaluated using the plasticity index method (PIM). ,e results showed a consistent improvement on the properties of the treated soil with the addition of the different activated admixtures. While the utilization of CARHA and HARHA improved the clayey soil to medium expansive soil, the treated clayey soil substantially improved from highly expansive soil with a potential of 23.35% to less expansive with a final potential of 0.59% upon the addition of 10% QARHA. Finally, QARHA was adjudged as the best binding composite due to the highest rate of reduction recorded with its utilization.
Keywords: Clayey Soil; Rice Husk Ash; Pavement Underlay; Plasticity Index Method (PIM)